The Impact of Compensation, The Company's Reputation and E-Recruitment of Job Application Interest - Randi Tangdialla; Rati Pundissing; Ade Lisa Matasik (LPPM Institut Bisnis dan Informatika Kesatuan, 2025)
Humans are social and individual beings thus they will always have desires, one of which is to have their needs met in a variety of ways. The purpose of this study is to examine how e-recruitment, pay, and firm reputation affect Generation Z's desire to apply for jobs in North Toraja. The goal is to determine how much each of these three aspects affects a candidate's decision to apply for a job and to offer suggestions for successful hiring practices that will help businesses draw in this digital generation. Because it has satisfied scientific criteria in a concrete or empirical, objective, quantifiable, rational, and methodical way, this study employs a quantitative method, a research approach founded on the positive philosophy (concrete facts). With a significant value of 0.738, the study's findings demonstrated that pay had no discernible impact on Generation Z's desire to apply for jobs in North Toraja. However, with significant values of 0.018 and 0.002, respectively, e-recruitment and firm reputation had a favourable and significant influence. Career advancement, location, and work experience are more important to Generation Z than pay. In conclusion, two important elements that influence interest in applying for employment are e-recruitment and corporate reputation.